Design of Real Time Walsh Transform for Processing of Multiple Digital Signals - Z. Zulfikar; Shuja A Abbasi; A. R. M. Alamoud (International Journal of Electrical and Computer Engineering (IJECE), 2013)
This paper presents the design and implementation of multiple digital signals processing using real-time Walsh transforms. The design of real time Walsh transform is done in such a way that it starts producing outputs instantly even before all input data have entered the system. The system consists of Walsh Transform circuit, several Digital Signal Processing (DSP) circuits, and an inverse Walsh transform circuit. The real time Walsh and inverse Walsh transforms are also designed to produce right results for any possible combinations of input data. DSP blocks are able to perform addition, subtraction, and dyadic convolution process of Walsh coefficients of more than one digital signals. Comparisons to the previous methods are briefly presented. It was found that the design of real time Walsh transform structure has better performance than many of the previously reported results in the literature.DOI:http://dx.doi.org/10.11591/ijece.v3i2.1965